Inducing Cellular Senescence in Cancer - Restall, Ian J. (Université d'Ottawa / University of Ottawa, 2013)
Cellular senescence is a permanent cell cycle arrest that is induced as a response to cellular stress. Replicative senescence is a well-described mechanism that limits the replicative capacity of cells and must be overcome by cancer cells. Oncogene-induced senescence (OIS) is a form of premature senescence and a potent tumor suppressor mechanism. OIS is induced in normal cells as a result of deregulated oncogene or tumor suppressor gene expression. An exciting area of research is the identification of novel targets that induce senescence in cancer cells as a therapeutic approach. In this study, a novel mechanism is described where the inhibition of Hsp90 in small cell lung cancer (SCLC) cells induced premature senescence rather than cell death. The senescence induced following Hsp90 inhibition was p21-dependent and the loss of p21 allowed SCLC cells to bypass the induction of senescence. Additionally, we identified a novel mechanism where the depletion of PKCι induced senescence in glioblastoma multiforme (GBM) cells. PKCι depletion-induced senescence did not activate the DNA-damage response pathway and was p21-dependent. Further perturbations of mitosis, using an aurora kinase inhibitor, increased the number of senescent cells when combined with PKCι depletion. This suggests that PKCι depletion-induced senescence involves defects in mitotic progression. Senescent glioblastoma cells at a basal level of senescence in culture, induced by p21 overexpression, and induced after PKCι depletion had aberrant centrosomes. Mitotic slippage is an early exit from mitosis without cell division that occurs when the spindle assembly checkpoint (SAC) is not satisfied. Senescent glioblastoma cells had multiple markers of mitotic slippage. Therefore, PKCι depletion-induced senescence involves mitotic slippage and results in aberrant centrosomes. A U87MG cell line with a doxycycline-inducible shRNA targeting PKCι was developed to deplete PKCι in established xenografts. PKCι was depleted in established glioblastoma xenografts in mice and resulted in decreased cell proliferation, delayed tumor growth and improved survival. This study has demonstrated that both Hsp90 and PKCι are novel targets to induce senescence in cancer cells as a potential therapeutic approach.
Keywords: senescence; hsp90; small cell lung cancer; geldanamycin; 17-aag; oncogene induced senescence; atypical protein kinase C; PKCiota; glioblastoma; mitotic slippage; mitotic slippage induced senescence; PKCι; p21; spindle assembly checkpoint